2021
DOI: 10.1101/2021.03.02.433573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of real-time fMRI denoising on online evaluation of brain activity and functional connectivity

Abstract: Objective: Comprehensive denoising is imperative in fMRI analysis to reliably evaluate neural activity from the blood oxygenation level dependent signal. In real-time fMRI, however, only a minimal denoising process has been applied and the impact of insufficient denoising on online brain activity estimation has not been assessed comprehensively. This study evaluated the noise reduction performance of online fMRI processes in a real-time estimation of regional brain activity and functional connectivity. Approac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…These processes can be completed in less than 400 ms for the whole-brain voxels on a current PC with a graphics processing unit (GPU) (Misaki and Bodurka, 2021). Thus, computation time does not limit today's real-time fMRI processing with a decent personal computer.…”
Section: Implementations Of the Online Fmri Denoising Processmentioning
confidence: 99%
See 4 more Smart Citations
“…These processes can be completed in less than 400 ms for the whole-brain voxels on a current PC with a graphics processing unit (GPU) (Misaki and Bodurka, 2021). Thus, computation time does not limit today's real-time fMRI processing with a decent personal computer.…”
Section: Implementations Of the Online Fmri Denoising Processmentioning
confidence: 99%
“…While the respiration volume per time (RVT) regressors (Birn et al, 2008) can also be made, we do not recommend using them in online processing. A previous study indicated that the online evaluation of RVT regressors could not be accurate, and its usage could introduce an artifactual signal fluctuation in real-time processing (Misaki and Bodurka, 2021). The RTP_RETROTS should receive cardiac and respiration signals in real-time.…”
Section: Implementations Of the Online Fmri Denoising Processmentioning
confidence: 99%
See 3 more Smart Citations